கந்தர்வன் கதைகளில் தொழிலாளர்கள் நிலை / Status of Workers in the Stories of Gandharvan - சி. ஆறுமுகம் / C. Arumugam (International Journal of Tamil Language and Literary Studies, 2024)
Man in the world has been living life without knowing the exact answer to their origin. The world that emerged from the Big Bang has evolved over millions of years and many species have appeared and are living in this world. Based on their intellectual capacity, living organisms are divided into semi-intelligent, intelligent and multi-intelligent species. Each living being passes through each stage of knowledge and emerges as each being, maturing and experiencing, with the longing to enjoy its highest pleasure. In Tamil culture, The best of all births is the human birth. It is worrying that even in this human birth, man could not live as a free man due to caste, religion and unethical social structure. In this case, every person tries to lead his life according to his place of birth, situation, economic background etc. All the working people in any part of the world belong to the same class. Liberation occurs in the lives of workers only when they unite as workers. Writers are capable of transforming the events of society into creative work. The Tamil Gandharvan has recorded in his works about the pathetic condition of industry and workers, the effects of capitalism on workers, the plight of poor workers and women workers and the life struggles of workers who want to be freed from them. Most of the Gandharvan stories are based on rural life, but he has made the stories based on the life of the workers in many of his stories to show the condition of the working labourers and their families. This article is intended to highlight the status of the working-class people and their plights in Tamil Nadu.